Psychoanalysis On Conflict Of The Main Character Hannah Baker In The 13 Reasons Why Series - Helena Nuarike Himan; Ni Ketut Sri Rahayuni; Nissa Puspitaning Adni (PT. Inovasi Teknologi Komputer, 2024)
It investigates the conflict of the main character and how she solve the conflict based on her personality. The primary aim of this study is to find out the various conflicts experienced by Hannah Baker and also to find out how she resolves the conflicts within the framework of her personality. This study used primary data from the TV Series 13 Reasons Why. It applied note-taking and documentation method. It also use qualitative method which focused on subjective assessment of attitudes, opinions and behaviour. The result of this study was presented in the informal method. There are two theories used in this study, which are theory of Conflict by Kenney which further explaining a conflict within a single man, a conflict between men, a conflict between man and society, and a conflict between man and nature (1966) and theory of Personality by Freud (1923), which further explaining about the id, ego and the superego of the main character’s personality. The first theory used for this study to answer the first problem of the study in finding out the conflict Hannah Baker encounter in her life. This examination aims to uncover the various dimensions of her conflicts. The second theory is used to answer the second problem of the study which is to find out the personality factors that delves into the intricate, unconscious aspects shaping individual personality that contributing in the main character Hannah Baker’s psychological state.